Effect of preoperative chlorhexidine, essential oil, and cetylpyridinium chloride mouthwashes on bacterial contamination during dental implant surgery: A randomized controlled clinical trial - Wael Yaghmoor; Montserrat Ruiz-Torruella; Yumi Ogata; Zuhair S. Natto; Matthew Finkelman; Toshi Kawai; Yong Hur (Elsevier, 2024)
Background: Although the role of chlorhexidine and other mouthwashes in periodontal therapy has been elucidated, little information is available on their use as routine preoperative mouth rinses before surgery, especially in periodontal procedures such as dental implant surgery. Objective: This study aimed to compare the efficacy of preoperative chlorhexidine, essential oil, and cetylpyridinium chloride mouthwashes in reducing bacterial contamination at the time of implant placement. Materials and Methods: Eligible patients who underwent dental implant surgery were randomly divided into four groups based on the mouthwash used: (1) 0.12 % chlorhexidine, (2) essential oil, (3) cetylpyridinium chloride, and (4) saline (served as the control group). All the patients of each group rinsed preoperatively with 15 mL of the respective mouthwash for 60 s. Saliva samples before (pre) and immediately after rinsing with the mouthwash (post) and after suturing the flap (end) were collected on the day of the implant placement. Real-time quantitative polymerase chain reaction (qPCR) was performed to analyze the samples and quantify the targeted periodontal pathogens using a propidium monoazide (PMA) dye. Results: Forty patients were included in the study. Real-time qPCR demonstrated a significant reduction in the number of pathogens in the saliva samples of the mouthwash groups compared to that of the control group. A statistically significant difference was observed between the groups for the pre-post and pre-end samples (p < 0.001) but not for the post-end samples (p = 0.203). A statistically significant difference was observed between the chlorhexidine, essential oil, and cetylpyridinium chloride mouthwash groups and the saline group (P < 0.001). The bacterial counts significantly differed with and without the use of the PMA dye. Conclusions: Preoperative chlorhexidine, essential oil, and cetylpyridinium chloride mouthwashes can reduce the bacterial load at the time of implant placement, thereby reducing the incidence of implant-related complications.